5(x-3)+6=5x-9

Simplify each term.

Apply the distributive property.

5x+5⋅-3+6=5x-9

Multiply 5 by -3.

5x-15+6=5x-9

5x-15+6=5x-9

Add -15 and 6.

5x-9=5x-9

5x-9=5x-9

Subtract 5x from both sides of the equation.

5x-9-5x=-9

Combine the opposite terms in 5x-9-5x.

Subtract 5x from 5x.

0-9=-9

Subtract 9 from 0.

-9=-9

-9=-9

-9=-9

Since -9=-9, the equation will always be true for any value of x.

All real numbers

The result can be shown in multiple forms.

All real numbers

Interval Notation:

(-∞,∞)

Solve for x 5(x-3)+6=5x-9